A Randomized Controlled Trial of a Pretransplant Educational Intervention in Kidney Patients. Issue 10 (October 2021) - Mansell, Holly; Rosaasen, Nicola; Wichart, Jenny; Mainra, Rahul; Shoker, Ahmed; Hoffert, Michele; Blackburn, David F.; Liu, Juxin; Groot, Brianna; Trivedi, Paraag; Willenborg, Errin; Amararajan, Maithiri; et al.
Abstract : Background: Poor patient knowledge about transplantation is a significant problem following kidney transplant. A video-based educational intervention was developed to supplement standard education provided by transplant teams. Methods: A multicenter randomized controlled trial tested the intervention delivered to patients undergoing assessment or waitlisted for kidney transplant. Adult participants were randomized to the control (standard education) or the intervention group, consisting of electronic access to the videos (or digital video disks if no internet) plus standard education. Differences between groups in changes in transplant knowledge (measured by the Kidney Transplant Understanding Tool), education satisfaction, self-efficacy, and quality of life (secondary outcomes) were evaluated by a preintervention and postintervention survey. Video viewing habits were tracked and described for patients in the intervention group. Results: One hundred sixty-two patients were enrolled, with 132 completing both questionnaires (n = 64 intervention and n = 68 control), with similar enrollment from 3 Canadian sites. Video viewing statistics in the complete cases indicated that 78% (50/64) watched the videos, with 70% (45/64) viewing them electronically, while 8% (5/64) received digital video disks and self-reported participation. Baseline knowledge scores in the intent-to-treat population were 55.4 ± 6.5 and 55.7 ± 7.1 in the intervention and control, respectively. The mean knowledge change in the intervention (2.1 ± 3.6) was significantly higher than in the control group (0.8 ± 3.4, P < 0.02). In the per-protocol analysis (patients with objective evidence of watching at least 80% of the videos), the knowledge improvements were 3.4 ± 3.8. Video group participants reported higher satisfaction with education ( P < 0.02) and expressed positive comments in open-ended feedback. Conclusions: Electronic video education in the pretransplant setting improved knowledge and satisfaction. Abstract : Supplemental Digital Content is available in the text.